Green Hydrogen Technical Interconnection Study in Isolated Island Grid - Riki Khomarudin; Shandy Last Febrino; Dzaky Satria Rahman Djuanda (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems))
The integration of Renewable Energy Plants, especially Hydrogen, is one of the considerations in supporting net zero emissions in 2025 by 23% following the renewable energy mix plan at RUPTL. To determine the network impact due to the integration of the Green Hydrogen Plant (GHP) with transient study scenarios, system reliability, and reserve margin. The method for determining the capacity of the Green Hydrogen Plant (GHP) is by looking at the Renewable energy quota allocated in the isolated grid area. From the results of the study obtained in this transient simulation, the system frequency value is still within safe limits in the grid code, where the results of the swing frequency value are at least 98.5%. For Power Angle stability, the lowest swing result of -700degree is obtained within 5 seconds. So the reactive power requirement is 0.75 MVar of the system in the swing requirement of the trip condition. The reliability index obtained by the system, when interconnecting with the Green Hydrogen Plant (GHP) has a better reliability level value. This can be seen from the index of disturbances saifi, saidi, caidi is getting lower. The system reliability index is still within safe limits following SPLN 68-2: 1986. In addition, the interconnection system with the Green Hydrogen Plant (GHP) has the highest reserve margin of 3.25 kW at 09:00, when the Green Hydrogen Plant starts production capacity of 5 MW.